Genomic Markers for Essential Tremor - Félix Javier Jiménez-Jiménez; Hortensia Alonso-Navarro; Elena García-Martín; Ignacio Álvarez; Pau Pastor; José A. G. Agúndez (MDPI AG, 2021)
There are many reports suggesting an important role of genetic factors in the etiopathogenesis of essential tremor (ET), encouraging continuing the research for possible genetic markers. Linkage studies in families with ET have identified 4 genes/loci for familial ET, although the responsible gene(s) have not been identified. Genome-wide association studies (GWAS) described several variants in LINGO1, SLC1A2, STK32B, PPARGC1A, and CTNNA3, related with ET, but none of them have been confirmed in replication studies. In addition, the case-control association studies performed for candidate variants have not convincingly linked any gene with the risk for ET. Exome studies described the association of several genes with familial ET (FUS, HTRA2, TENM4, SORT1, SCN11A, NOTCH2NLC, NOS3, KCNS2, HAPLN4, USP46, CACNA1G, SLIT3, CCDC183, MMP10, and GPR151), but they were found only in singular families and, again, not found in other families or other populations, suggesting that some can be private polymorphisms. The search for responsible genes for ET is still ongoing.